Respostas
respondido por:
1
Resposta:
(2x+4)*(-x²+1)<= 0
p=2x+4 ..a=2>0 ..raiz = -2
p---------------------------(-2)++++++++++++++++
q=-x²+1 ..a=-1<0 ...concavidade p/baixo
raízes x'=-1 e x''=1
q---------------------(-1)+++++++++++++++(1)---------------------
Estudo de Sinais:
p-------------(-2)++++++++++++++++++++++++++++++++++++
q-------------------------(-1)+++++++++++++++(1)---------------------
p/q++++++(-2)-------(-1)+++++++++++++++(1)--------------------
-2≤ x ≤ -1 U x ≥ 1 é a resposta
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás